Modeling and estimating shadow sovereign ratings - Zoran Ivanovic; Sinisa Bogdan; Suzana Baresa (Contemporary Economics, 2015)
This paper describes and evaluates "shadow" sovereign credit ratings, which represent the credit ratings of countries that are not rated by credit rating agencies. Credit ratings represent the creditworthiness of companies or governments. They are important in attracting foreign capital. Countries without credit ratings can face greater difficulties than countries with low credit ratings, for example paying a higher price for capital. This paper has two objectives. The primary objective of this paper was to estimate a rating prediction model to the assess credit ratings of countries that are not yet rated. Large numbers of potential determinants were tested, and nine variables were selected that play a key role in assessing credit ratings. According to the chosen determinants, a highly precise model was calculated (80% of the estimated ratings were identical to the corresponding actual ratings or only one notch different). The purpose of this analysis was to estimate credit ratings for a sample of 31 unrated countries. The results are statistically significant and explained in detail. The second objective of this paper was to demonstrate that countries that are not ranked would not necessarily receive the lowest rating, and the results supported that hypothesis.
Keywords: G24; 330; credit rating agency; credit ratings; determinants of sovereign credit ratings; Standard & Poor's; unrated countries